Renewable Energies In Algeria: A Study Of Potential And Opportunities - Bouachiba, Aicha (المجلة الجزائرية للأمن الإنساني, 2020)
Renewable energies are increasingly being recognized as one of the most important sources of clean energy to which the world pays special attention. Algeria is one of the countries with a wide range of renewable energies, many of which remain unexploited. There is a great gap between the possibilities available and the actual resources exploited Considering that renewable energies are among the new approaches to reach development, we are trying to shed light on the most important projects adopted by Algeria in this context, which can drive the pace of sustainable development. The research concluded that Algeria had large untapped renewable energies.